Phage therapy against Enterococcus faecalis in dental root canals. Issue 1 (1st January 2016) - Khalifa, Leron; Shlezinger, Mor; Beyth, Shaul; Houri-Haddad, Yael; Coppenhagen-Glazer, Shunit; Beyth, Nurit; Hazan, Ronen
Abstract : Antibiotic resistance is an ever-growing problem faced by all major sectors of health care, including dentistry. Recurrent infections related to multidrug-resistant bacteria such as methicillin-resistant Staphylococcus aureus, carbapenem-resistant Enterobacteriaceae, and vancomycin-resistant enterococci (VRE) in hospitals are untreatable and question the effectiveness of notable drugs. Two major reasons for these recurrent infections are acquired antibiotic resistance genes and biofilm formation. None of the traditionally known effective techniques have been able to efficiently resolve these issues. Hence, development of a highly effective antibacterial practice has become inevitable. One example of a hard-to-eradicate pathogen in dentistry is Enterococcus faecalis, which is one of the most common threats observed in recurrent root canal treatment failures, of which the most problematic to treat are its biofilm-forming VRE strains. An effective response against such infections could be the use of bacteriophages (phages). Phage therapy was found to be highly effective against biofilm and multidrug-resistant bacteria and has other advantages like ease of isolation and possibilities for genetic manipulations. The potential of phage therapy in dentistry, in particular against E. faecalis biofilms in root canals, is almost unexplored. Here we review the efforts to develop phage therapy against biofilms. We also focus on the phages isolated against E. faecalis and discuss the possibility of using phages against E. faecalis biofilm in root canals.